Analisis Penguatan Peran Dewan Perwakilan Daerah dalam Sistem Konstitusional Indonesia (Studi Perbandingan dengan Senat Spanyol) - Mochammad Farhan; Ende Hasbi Nassaruddin; Wawan Kurniawan (Fakultas Hukum Universitas Islam Malang, 2026)
The constitutional dysfunction of the Regional Representative Council of the Republic of Indonesia has resulted in weak regional representation in national policy. This study employs a normative legal methodology with a legislative. conceptual and comparative law approach based on Konrad Zweigert’s theory of legal style; it analyzes the transformation of the Regional Representative Council by drawing on the model of the Spanish Senate. The results of the study indicate that the Spanish Senate possesses authoritative procedural leverage, whereas in Indonesia, the absence of such leverage results in regional aspirations being consistently dominated by political party coalitions within the People’s Representative Council. Through this strengthening, the Regional Representative Council transforms into a functional counterbalance that ensures justice for all regions of the archipelago.